Comment on “Dissociation and re-imagination: the publicity of Chinese marriage law and divorce narrative in 1950” - Fangyuan Sun (Trans/Form/Ação, 2024)
Commented Article: LUO, Yingyu; HAN, Chao. Dissociation and Re-Imagination: The Publicity of Chinese Marriage Law and Divorce Narrative in 1950. Trans/Form/Ação: Unesp Journal of Philosophy, v. 47, n. 4, e0240056, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14535.